Analysis of the Design of the Palm Frond Chopping Machine as a Basic Ingredient for Animal Feed - Imam Hanafi; Anis Siti Nurrohkayati (Universitas Muhammadiyah Sidoarjo, 2022)
Currently, organic waste is still underutilized. If managed properly, it will produce a sale value and can also be used for various purposes. Organic waste that is still underutilized is like palm fronds. In areas especially Kalimantan, oil palm plantations are very common, the harvesting system in oil palm plantations produces fresh fruit bunches (FFB) and waste in the form of palm fronds which are piled up between the oil palm plants (gangan mati). The purpose of this research is to make a machine that can chop oil palm fronds into animal feed. Before making a coconut frond chopping machine, the design and force calculations are made first. The amount of torque obtained is 1,300 kg.f.mm, the motor power used in the initial design is 3 Hp, and the length of the belt used using pulley 1 with a diameter of 100 mm and pulley 2 with a diameter of 150 mm is A55 inch.